2001
DOI: 10.1097/00125817-200101000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Taking advantage of early diagnosis: Preschool children with the 22q11.2 deletion

Abstract: Purpose: The purpose of this study is to review the neurodevelopmental outcome of infants and preschoolers with a 22q11.2 microdeletion and to discuss the our clinical observations of clinical implications for educational and therapeutic interventions. Methods: One hundred twelve children (4 to 70 mos) with the 22q11.2 deletion were assessed using standardized tests (Bayley Scales of Infant Development-II, Preschool Language Scales, WechslerPreschool and Primary Scales of Intelligence-Revised). Results: Fifty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
71
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 19 publications
9
71
1
Order By: Relevance
“…33 Learning disability is frequently found, especially nonverbal learning disorder, though there is variation in the type and extent of learning disability. 26,33,40 Further complicating learning and school performance is the fact that attention deficit hyperactivity disorder (ADHD) is more common in 22q11DS patients than in the general population. One study found that ADHD occurs in about 30% of patients with 22q11DS.…”
Section: Cognitive/developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Learning disability is frequently found, especially nonverbal learning disorder, though there is variation in the type and extent of learning disability. 26,33,40 Further complicating learning and school performance is the fact that attention deficit hyperactivity disorder (ADHD) is more common in 22q11DS patients than in the general population. One study found that ADHD occurs in about 30% of patients with 22q11DS.…”
Section: Cognitive/developmentmentioning
confidence: 99%
“…For example, learning problems are a nearly uniform feature of the syndrome, and early intervention is important in bringing about the best possible outcome. 40 Early intervention services are appropriate for ensuring that these patients reach their highest potential, and a screening test could help make sure that all affected individuals are included in these programs. A definitive diagnosis may also be helpful in securing appropriate special education services for these children as they enter higher grades.…”
Section: Cost Considerations Benefitsmentioning
confidence: 99%
“…This fact is even more relevant if one takes into account the potential benefit of preventive measures that could be applied if such a diagnosis were defined (12).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, facial features may not be apparent in infants, renal findings are not evident upon routine examination (10), and the characteristic speech and learning difficulties typically do not become clear until beyond infancy (11). Therefore, an early diagnosis of a 22q11 deletion in infants with congenital cardiovascular disease allows for early detection of associated noncardiac features, as well as appropriate genetic counseling (9,12). These findings broaden the classical indications for testing, warranting screening for 22q11.2 deletion in infants with sporadic congenital heart disease as well.…”
Section: Introductionmentioning
confidence: 99%
“…Children with a del22q11 commonly have learning difficulties, 3,4 speech-language problems, 5,6 and an attention-deficit disorder. 7 Previous studies reported deficits in the acquisition of gross motor skills (crawling and walking independently) [8][9][10][11] and problems with balance and coordination. 3,11,12 In a recent study by Swillen et al, 13 the motor development of young children (aged between 2 and 5y) with del22q11 and a CHD was compared with a control group of children without a del22q11 matched for age and type of CHD.…”
mentioning
confidence: 99%